Upaya Pencegahan Anak sebagai Korban Kekerasan Seksual melalui Dunia Maya - Desak Ketut Linda Saraswati; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Since being in the womb, the child has dignity as a whole human being given by God Almighty. A child who is born must get his rights without the child asking. Children who are part of the next generation with the ideals of the nation have a strategic role in ensuring the existence of the nation and state in the future. Sexual violence against children today does not only occur physically but has penetrated cyberspace. This is because it is easy to access cyberspace, especially social media, by various groups ranging from children, adolescents and even parents. This study uses the normative legal method, namely a library research to obtain legal materials. The results of the analysis show that prevention can be done through preventive and repressive measures. Preventive efforts through a family environment that implements the 18-21 program, which means that at 18.00 to 21.00 the time for children and parents to have dialogue and interaction, which was first implemented in Padang City. Besides parents, so that they can give more time and attention to children. Repressive measures are taking action against perpetrators of sexual violence against children through cyberspace in accordance with applicable laws and regulations so that the perpetrators have a deterrent effect and do not repeat it on another day.